THE MASTER OF PUBLIC ADMINISTRATION DEGREE: NATIONAL UNIVERSITY’S ACADEMIC TRAINING MISSION IN THE PEOPLE’S REPUBLIC OF CHINA - Far, Maryam Davodi (PEOPLE: International Journal of Social Sciences, 2017)
This concept paper considers public administration education in China and whether there is opportunity for National University to consider the expansion and growth of its public administration programs in China. Considering China’s National Outline for Medium and Long Term Educational Reform and Development, drivers for change in Chinese public administration, and the competitive landscape for graduate studies in public administration with study abroad programs characterize a potential opportunity for expansion and growth of National University’s public administration programs in China.